XRF mapping and TEM analysis of coated and uncoated silica nanoparticles in A549 cells and human monocytes. (4th January 2019) - Rio‐Echevarria, Iria M.; Ponti, Jessica; Bogni, Alessia; Gilliland, Douglas; Altissimo, Matteo; Pascolo, Lorella; Ceccone, Giacomo; Gianoncelli, Alessandra
Abstract : The evaluation of nanomaterials intracellular distribution still remains a challenge in nanomedicine applications and toxicological studies. Synchrotron radiation X‐ray microscopy combined with X‐ray fluorescence (XRF) microspectroscopy provides unique information that has pushed the frontiers of biological research, particularly when investigating intracellular mechanisms. In this work, the presence of silica nanoparticles in in vitro cultured human lung epithelial cell line and freshly extract human monocytes has been investigated. For the uptake and intracellular distribution of NPs, cells were cultured on polymeric substrates (Mylar). The SiO2 –NPs have been synthesized at JRC and characterized by dynamic light scattering, centrifugal liquid sedimentation, and transmission electron microscopy (TEM), whereas their interaction with cells was investigated with TEM and XRF. For the latter, we used TwinMic in scanning transmission mode coupled with low‐energy XRF spectroscopy, paying particular attention to the distribution of different elements, namely, Fe, O, C, Si, and Mg. Si XRF signals recorded on cells exposed to uncoated silica and epoxy‐coated silica nanoparticles are comparable, indicating low difference in cellular uptake and suggesting a similar interaction between nanoparticles and cells. However, the TEM analysis indicates a better affinity of the coated nanoparticles for the cell membrane. Moreover, the TEM analysis shows also the presence of nanoparticles in endosomes.